(untitled) (Journal of Association of Educational Management and Policy Practitioners, 2025)
Artificial intelligence (AI) is rapidly transforming various industries, including education. AI is being used in educational management to enhance the learning process, improve student outcomes, and streamline administrative tasks. This research work aims to explore the application of AI in educational management, including its benefits and challenges. The research work employs a systematic review methodology, examining the literature on AI in educational management. The study finds that AI has several advantages, including improving student engagement, personalization of learning, and cost-effectiveness. However, AI also poses several challenges, such as ethical concerns, potential biases, and the need for re-skilling the workforce. The research concludes that AI has an enormous capacity to improve educational management, but it must be deployed with care and caution. Machine learning in education can automate time -consuming task like grading essays, freeing up valuable educator time for more personalized guidance ML powered feedback systems can also provide students with immediate insights into their performance, allowing them to identify areas for improvement on their own. Suggestion. personalized learning AI can be used to create personalized learning, data analysis, AI can analyze vast amounts of data to identify trends, virtual tutors, administrative tasks.